COMPUTER MODELING OF TRANSIENT HEAT CONDUCTION IN AXISYMMETRIC BODIES USING THE FINITE ELEMENT METHOD - Sapayev, Shikhnazar Omonovich; Matyakubov, Marks Yakhshimuradovich (SCIENCE and SOCIETY, 2026)
The paper considers the analysis of transient heat conduction processes in axisymmetric bodies based on the finite element method. The problem is reduced to an equivalent two-dimensional formulation through the cross-section of the body. Based on this approach, a numerical model is developed, a solution algorithm is designed, and corresponding software is implemented.